Boundary-Spanning Care: Reducing Psychiatric Rehospitalization and Self-Injury in a Jail Population. (October 2018) - Bursac, Rahela; Raffa, Laura; Solimo, Angela; Bell, Connor; Ford, Elizabeth
Individuals with serious mental illness detained in jail may require frequent psychiatric hospitalization due to the destabilizing nature of the jail environment. This study examined the impact of a pilot treatment program involving continuity of patient care across jail and hospital settings aimed at reducing hospitalizations and negative health outcomes for a population of high-risk, incarcerated individuals with mental illness. This study examined rate ratios of psychiatric hospitalizations, injuries, and suicide watches, comparing 15 patients in the treatment program to themselves pretreatment and to a control group of 15 frequently rehospitalized patients. Patients in treatment experienced significant decreases in overall hospitalizations ( p < .001), 15-day rehospitalizations ( p < .002), and suicide watches in jail ( p < .02), compared to themselves pretreatment. A boundary-spanning treatment program lowered hospitalization rates and need for suicide watch for a small, yet clinically complicated and challenging group of patients.